Beyond the indigenous/non-indigenous knowledge divide: The case of Muslim education and its attenuation to cosmopolitanism - Davids, Nuraan; Waghid, Yusef (South African Journal of Higher Education, 2016)
Muslim education can be understood to be constituted and framed by three discernable, yet inter-related epistemological and ethical practices, namely, tarbiyyah (socialisation), ta’līm (critical engagement), and ta’dīb (social activism). Its distinctiveness as an indigenous knowledge system is shaped by its role and function in both the educational and daily expressions of Muslim life. What this means is that Muslim education, as enacted through tarbiyyah, ta’līm, and ta’dīb, not only fulfils the role of offering Muslims foundational understandings of their faith, but it also advances the social practices necessary for Muslims to be adherents of Islam, and what that ought to mean in relation to their social and humane contexts and responsibilities. Now, if Muslims, by virtue of the epistemological and ethical practices of Muslim education, are expected to understand Islam not only in terms of their own faith and practices, but in terms of how they enact those practices in relation to all others, then what defines a Muslim community, and by extension, an indigenous Muslim knowledge system? In commencing with an exploration of the concept of knowledge in Muslim education, we question whether the notion of an indigenous knowledge system is indeed a plausible one. Secondly, in turning to cosmopolitanism, we consider whether the classification of knowledge into indigenous and non-indigenous systems might serve to undermine humane enactments of social and moral responsibilities, rather than to enhance it.